The Recent Progresses on The Improved Therapy of Melanoma by Novel Drug Delivery Systems - Taymouri, Somayeh; Varshosaz, Jaleh (Current Drug Targets, 2014)
Melanoma is a life threatening disease with a growing incidence rate. It is estimated that 9840 patients will die from melanoma in 2014. Despite numerous attempts for treating metastatic melanoma, conventional therapies including systemic chemotherapy or immunotherapy, either as single agents or combined, have not been promising. The most cytotoxic agents have low molecular weight, which leads to rapid excretion, nonspecific distribution, and poor therapeutic index. Therefore, they may even increase toxicity due to their non-specific action on healthy tissue that can exacerbate the malady. To provide optimum effective concentration, multiple-dose drug administration is required, which again can increase the incidence of adverse effects. Recent developments in drug delivery systems are able to improve the drug efficacy and safety, and offer more promising approaches in treating melanoma. Recent researches have shed more light on the advantages of novel drug loaded carrier systems versus free drugs. Most of these animal studies, reported improvement in treatment efficacy and survival rate using novel carrier systems. This is related to the ability of these systems in enhancing the anticancer effect by modifying drug pharmacokinetics and biodistribution, selective target delivery of the agents to the diseased tissue and their ability to cross the biological barriers. In this paper, it is attempted to illustrate the potentials of novel strategies in treatment of melanoma incorporating drug delivery systems versus conventional therapies.
Keywords: ultrasound